2017
DOI: 10.1097/mou.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in staging and imaging for penile cancer

Abstract: Over the past decade, staging and treatment of penile cancer have become less invasive, while survival tends to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Although, our diagnostic evaluation including US‐guided FNA followed by DSNB showed a low number of false negatives, further improvements of this diagnostic workflow should be explored. For example repeated FNA in men with palpable LNs, which would allow timely ILN dissection and avoid DNSB because of false negative US‐guided FNA results [19]. An additional interesting research approach represents radiomics using US [20] or cross‐sectional images [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although, our diagnostic evaluation including US‐guided FNA followed by DSNB showed a low number of false negatives, further improvements of this diagnostic workflow should be explored. For example repeated FNA in men with palpable LNs, which would allow timely ILN dissection and avoid DNSB because of false negative US‐guided FNA results [19]. An additional interesting research approach represents radiomics using US [20] or cross‐sectional images [21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed a very high accuracy (up to 93%) of MRI for clinical nodal staging to predict pathological LN involvement (11) and the use of pelvic MRI to assess the local extent of tumor and regional LN enlargement is highly recommended in the current guidelines (6). In contrast, a recent meta-analysis reported an only 57% sensitivity of PET/CT in detecting LN metastasis in clinically negative groin, and using PET/ CT in patients with distal urethral SCC with clinically negative groins was not recommended (15,16). In the current study, a false positive result was shown on PET/CT, probably indicating a potentially unsatisfactory specificity of PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging can also help to identify metastatic disease or other affected lymph nodes in the chest, abdomen, or pelvis. 50 It is important to note that imaging is a useful adjunct to physical examination. Indeed, as much as 16% of patients without palpable lymphadenopathy may harbor occult metastatic disease, and 20–40% of patients with palpable lymphadenopathy are found to be non-metastatic.…”
Section: Imaging For Nodal and Metastatic Diseasementioning
confidence: 99%